Dynamic influence of international price fluctuation on soybean market price in China: based on Bayesian-VAR model - Xu, Xiaocang; Cai, Shuangshuang; Zhang, Lingyu (Frontiers in Sustainable Food Systems, 2025)
ContextUnder the suppression of Trump 2.0 tariffs in the United States, fluctuations in agricultural product prices have become one of the significant risks to the security of China’s supply chain, especially for soybeans which are greatly affected by the US market.MethodologyBased on the monthly data of international and Chinese soybean futures prices and spot prices from May 2008 to October 2024, this paper constructs a Bayesian VAR model to explore the transmission path of international price fluctuations to Chinese soybean futures and spot prices.InnovationDifferent from many previous studies, this paper adopts the Bayesian VAR model, which can alleviate overfitting more effectively than the VAR model, improve the prediction accuracy, and reflect the dynamic impact of price fluctuations more accurately.ConclusionThe results show that fluctuations in international market prices have a significant price discovery effect on the Chinese soybean market, which can help participants in the upstream and downstream of the supply chain reduce the risk of price fluctuations in the short term. However, the hedging function of the futures market still needs to be improved in the long term.